2015
DOI: 10.1007/s10096-015-2408-8
|View full text |Cite
|
Sign up to set email alerts
|

Impact of borderline minimum inhibitory concentration on the outcome of invasive infections caused by Enterobacteriaceae treated with β-lactams: a systematic review and meta-analysis

Abstract: Minimum inhibitory concentrations (MICs) have been used to denote susceptibility in vitro and to guide clinical practice. Our objective was to investigate whether the clinical outcomes of patients with invasive infections caused by Enterobacteriaceae treated with β-lactams were worse among those with a borderline susceptible MIC according to European Committee on Antimicrobial Susceptibility Testing (EUCAST) breakpoints than those with a lower MIC. Studies reporting MICs of β-lactams used for infection and cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…A “susceptible” MIC value close to clinical breakpoint could indicate that the antibiotic could be less effective than what can be expected from a strain with a much lower MIC far from the clinical breakpoint. Our data go in the same meaning as Torres et al who have recently shown that “highly susceptible” isolates are associated with higher clinical cure rates than “borderline isolates”[ 22 ].This consideration should be taken into account when choosing between different antibiotic that are all “susceptible”.…”
Section: Discussionsupporting
confidence: 80%
“…A “susceptible” MIC value close to clinical breakpoint could indicate that the antibiotic could be less effective than what can be expected from a strain with a much lower MIC far from the clinical breakpoint. Our data go in the same meaning as Torres et al who have recently shown that “highly susceptible” isolates are associated with higher clinical cure rates than “borderline isolates”[ 22 ].This consideration should be taken into account when choosing between different antibiotic that are all “susceptible”.…”
Section: Discussionsupporting
confidence: 80%
“…Examining the effect of PTZ MIC on outcomes with non-ESBL infections has not shown a difference. 29,30 Different infection sites and organisms in this study diminish the external validity of the effect of MIC on mortality and cure.…”
Section: Mic Impact and Future Studiesmentioning
confidence: 88%
“…Since isolates with MICs near the breakpoint have lower clinical response to the antibiotic [6][7][8] , the choice between two antibiotics with the same MIC for the same pathogenic isolate but with two different clinical breakpoints would likely benefit from consideration of this 'distance' to the breakpoint. This is especially true for immunocompromised patients, who need antibiotics with high bactericidal activity because of their impaired immune system [10] .…”
Section: Discussionmentioning
confidence: 99%
“…Pseudomonas aeruginosa isolates showing borderline MICs (near the breakpoint) may be at higher risk of clinical failure, even mortality, than those with infections having lower MICs [6,7] . Similarly, Falagas et al found that more treatment failures occurred in patients infected with Salmonella enterica strains with high fluoroquinolone MICs (near the breakpoint) than those with Salmonella strains with low MICs, and mortality rate for patients infected by Gram-negative non-fermentative bacilli with high MICs was also higher than for those with low MICs [8] .…”
Section: Patients Infected With Gram-negative Enterobacteriaceae Ormentioning
confidence: 99%